Evaluasi Strategi Bersaing Teh Botol Sosro di Kota Surakarta (Pendekatan Competitive Profile Matrix) - Inesya Nur Rohmah; Heru Irianto; Minar Ferichani (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
The increasing popularity of packaged tea beverages has encouraged many companies to launch tea drink products and compete to gain positive consumer responses. This competitive condition demands that Teh Botol Sosro understand its market position and develop effective strategies to maintain and expand its market share. Therefore, this study applies the Competitive Profile Matrix (CPM) to analyze Teh Botol Sosro's market position in Surakarta, the first study in this context. The research aims to identify the key competitive factors, evaluate Teh Botol Sosro's position, and formulate alternative strategies to enhance its competitiveness. The research method is descriptive, with a purposive location selection in Surakarta. Key informants include the Area Sales Manager, Sales Supervisor, and Distributor Supervisor of PT Sinar Sosro in Surakarta City, with samples selected using accidental sampling. The data used includes primary and secondary data collected through observation, interviews, and documentation, then analyzed using the CPM analytical tool. Research findings showed that the primary competitive factors for Teh Botol Sosro include freshness of taste, tea fragrance, product size variations, packaging design, price, advertising, brand image, discounts, and distribution. Based on the CPM, Teh Botol Sosro ranks second, excelling in brand image, advertising, packaging design, and product size variations, but still competes closely with Teh Pucuk Harum, which holds the first position. The recommended alternative strategies include (1) maintaining performance on superior attributes, (2) benchmarking against competitors in aspects of freshness of taste, tea fragrance, nutrition, and price, and (3) enhancing discount and distribution strategies. This study is expected to provide insights into understanding the factors influencing consumer preferences and support the development of adaptive agribusiness strategies in the ready-to-drink tea industry.